2012
DOI: 10.1002/imhj.20333
|View full text |Cite
|
Sign up to set email alerts
|

Implications of homelessness for parenting young children: A preliminary review from a developmental attachment perspective

Abstract: Although it has been well-documented that parents and children who experience homelessness often have compromised health and well-being, few studies have examined the potential implications of homelessness on the process of parenting young children. In this review, we consider how parents of young children might function under the circumstances of homelessness. We begin with a brief overview of the psychological, social, and medical characteristics of homeless mothers and their young children. Using a developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 38 publications
3
52
0
3
Order By: Relevance
“…Mothers' preoccupation with basic survival, as well as the physical, emotional and financial strains of homelessness stress their capacity to respond fully to children's needs (David et al, 2012). On the other hand, homeless children younger than 6 years old are especially vulnerable to developing emotional and behavioral disorders compared to school-age children and adolescents (Shinn et al, 2008).…”
mentioning
confidence: 99%
“…Mothers' preoccupation with basic survival, as well as the physical, emotional and financial strains of homelessness stress their capacity to respond fully to children's needs (David et al, 2012). On the other hand, homeless children younger than 6 years old are especially vulnerable to developing emotional and behavioral disorders compared to school-age children and adolescents (Shinn et al, 2008).…”
mentioning
confidence: 99%
“…vaccination) to all children regardless of their parents' administrative or health care characteristics, could improve access to health care for families with psychological difficulties [77]. In particular, the structures could extend children's follow-up beyond age 6, and improve screening of parent mental health and parental difficulties [79,80]. Some studies show the effectiveness of interventions designed to develop children's psychosocial skills and parental abilities [81][82][83][84][85][86].…”
Section: Clinical and Policy Implicationsmentioning
confidence: 99%
“…Children born to teenage mothers (Coker, Meyer, Smith, & Price, 2010; David, Gelberg, & Suchman, 2012; Swick & Williams, 2010; Yordan & Yordan, 1993) and those born to mothers with lower educational attainment (Rouse & Fantuzzo, 2009; Duffield & Lovell, 2008; David, Gelberg & Suchman, 2012) are more likely to experience periods of homelessness. Children who experience homelessness are also much more likely to experience child maltreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Biological vulnerabilities and health threats are also disproportionately associated with early homelessness. Research studies have shown that children who experience homelessness are more likely to evidence birth risks, including inadequate prenatal care (David, Gelberg & Suchman, 2012) and preterm birth (Rouse & Fantuzzo, 2009), than their housed peers. These vulnerabilities are exacerbated by low quality housing, including exposure to high rates of lead concentration due to the lead-based paint found in poor housing conditions (Kerker et al, 2011; Rafferty and Shinn, 1991).…”
Section: Introductionmentioning
confidence: 99%